MAIN FACTORS THAT CONTRIBUTE TO THE REDUCTION OF PARTICIPATION IN SPORTS ACTIVITIES AMONG UNIVERSITY STUDENTS - Mihai OLĂNESCU (Cluj University Press, 2021)
Introduction: In this article, our aim is to examine the main reasons that lead university students to practice less and less physical sports activities. Objective: Identifying the differences that may exist between students who were enrolled at the Technical University of Cluj-Napoca, in the academic year 2011-2012, and those who were enrolled in the academic year 2019-2020, regarding the reasons that determine them to reduce the time allocated to physical sports activities. Methods: To find out why the level of participation of university students in various physical sport activities is very low, and tends to decrease from year to year, we conducted two studies, the first one in the 2011-2012 academic year (n=880 participants), and the second one, in the academic year 2019-2020 (n=594 participants), and we compared the results obtained. Results: The results of the study show the reasons for today's short time allocated by students to physical activities and the reasons why they are too busy to play sports. The findings indicate that the main reason why students of the Technical University of Cluj-Napoca practice less and less physical sports activities is because they are busier. The overloaded program from university is the main cause why some students have reduced the time allocated to sports activities. Other important factors are the lack of energy and the lack of sport facilities. Conclusions: Increasing educational requirements and reduced leisure time, justify a decrease in students' interest in participating in extracurricular sports activities. To increase the motivation and future sport adherence of students, it would be necessary for universities and local public authorities to provide a motivational climate for practicing physical activities and sport.   REZUMAT. Factorii principali care contribuie la reducerea participării la activități sportive în rândul studenților. Introducere: Scopul acestui articol este de a examina principalele motive care îi determină pe studenți să practice din ce în ce mai puține activități fizice sportive. Obiective: Identificarea diferențelor care pot exista între studenții care au fost înscriși la Universitatea Tehnică din Cluj-Napoca, în anul universitar 2011-2012, și cei înscriși în anul universitar 2019-2020, cu privire la motivele care îi determină să reduce timpul alocat activităților fizice sportive. Metode: Pentru a afla de ce nivelul participării studenților la diferite activități fizice sportive este foarte scăzut, și tinde să scadă de la an la an, am efectuat două studii, primul în anul universitar 2011-2012 (n = 880 participanți), și al doilea, în anul universitar 2019-2020 (n = 594 participanți), și am comparat rezultatele obținute. Rezultate: Rezultatele studiului arată motivele pentru care studenții alocă puțin timp activităților fizice și de ce sunt prea ocupați pentru a face sport. Principalul motiv pentru care studenții Universității Tehnice din Cluj-Napoca practică din ce în ce mai puține activități sportive este faptul că sunt mai ocupați și au mai puțin timp liber. Programul încărcat de la universitate este principala cauză pentru care unii dintre studenți au redus timpul alocat activităților sportive. Alți factori importanți sunt lipsa de energie și lipsa facilităților pentru practicarea sportului. Concluzii: Creșterea cerințelor educaționale și reducerea timpului liber, justifică scăderea interesului studenților de a participa la activități sportive extrașcolare. Pentru a spori motivația și aderarea sportivă viitoare a studenților, ar fi necesar ca universitățile și autoritățile publice locale să ofere un climat motivațional pentru practicarea activităților fizice și a sportului. Cuvinte cheie: activitate fizică, sport, populație studențească, timp liber, motivație.